The Kingfisher book of living worlds - Gifford, Clive (Kingfisher London, 2002)
This title celebrates the diversity of the natural world. It aims to bring to life the complex relationships between different species and their environment, from the bizarre communities that thrive around undersea volcanic vents to the amazing adaptations of polar creatures.